Oracle WebLogic Server 12c Administration I Exam 1Z0-133 A Comprehensive Certification Guide - Garnica, Gustavo (Apress, 2018)
Use this comprehensive guide to study for the Oracle WebLogic Server 12c Administration I Exam 1Z0-133. This book is a unique introductory resource to the WebLogic Server certification for new Oracle Fusion Middleware administrators and a valuable resource for veteran WebLogic Server administrators seeking to update their skills for the 12c certification topics. It is common sense that passing a certification exam requires a good command of the subject matter, understanding the intricacies surrounding its practice, and having sufficient experience working with the concepts. This book aims to accelerate the process by providing an accurate review of all exam topics, suggesting hands-on practices to gain or reinforce experience working with WebLogic Server, and introducing questions to help candidates become familiar with the format and style of questions found on the actual certification exam. Oracle WebLogic Server 12c Administration I Exam 1Z0-133 covers the associate level certification with Oracle. Although not dedicated to exam 1Z0-599, the guide is also a valuable foundational resource for those preparing for WebLogic Server 12c implementation specialist level certification. This book: Inspects the certification topics in the order that you would likely follow in an on-the-job middleware infrastructure project Is a great resource for candidates preparing for the certification, who are unable to start with live or personally-assisted training Is a great starting point for those pursuing advanced Oracle WebLogic Server certifications What You'll Learn: Cover all topics on the certification exam 1Z0-133 Become familiar with the types and format of questions on the certification exam Understand and properly describe Oracle WebLogic Server domains and clusters Install, configure, maintain, and monitor Oracle WebLogic Server Deploy and manage applications on Oracle WebLogic Server Discover how to use new administration features of Oracle WebLogic Server 12c.